Effect of Nigella Sativa (Black Cumin), Vitamin E and their Combination on Metoprolol Induced Hepatotoxicity in Rabbits - Fatima Hussein; Jawad Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Metoprolol (MET) is a selective Beta-1 blocker. It is metabolized in the liver. Unlike mostBetablockers, Metoprolol is unique in causing liver toxicity, which is infrequent, ranging from raised liverenzymes to severe liver damage. Aim: hepatotoxicity was induced in rabbits, and protective effects ofNigella sativa (NS), Vitamin E (Vit E), and a combination of Nigella sativa + Vitamin E were investigatedon Metoprolol-induced hepatotoxicity.Methods: 36 male rabbits were divided into six groups and treated as follow: Metoprolol (20mg/kg),Nigella sativa (2ml/kg), control group, Metoprolol + Nigella sativa, Metoprolol + Vitamin E ( 175mg/kg/day), Metoprolol + Nigella sativa + Vitamin E. Treatments were given orally for two weeks. Liverenzymes, malondialdehyde, glutathione, and interleukins (IL-6, IL-10) were measured in serum and liverhomogenates. Histopathological examinations were done for two animals in each group.Results: Elevated liver enzymes and histopathological changes were seen in all Metoprolol-treated animals.Nigella sativa, Vitamin E, and Nigella sativa + Vitamin E reduced Metoprolol-induced rise in liver enzymes.Metoprolol increased malondialdehyde concentration in serum and liver homogenate. Treatment withNigella sativa, Nigella sativa + Vitamin E insignificantly decreased these levels. Neither Metoprolol norMetoprolol and Nigella sativa, Vitamin E, and their combination changed the levels of IL-6 or IL-10.Conclusion: Metoprolol increased liver enzymes, and treatment with Nigella sativa, Vitamin E, and Nigellasativa + Vitamin E significantly modified rise in liver enzymes. Metoprolol and other treatments had littleeffect on IL-6 or IL-10.